Combined branched-DNA and conventional HBV PCR assays for detection of serum HBV-DNA in hepatitis B e antigen-positive chronic hepatitis B patients - Ozdarendeli, A; Toroman, ZA; Bulut, Y; Demirbag, K; Kalkan, A; Ozden, M; Kilic, SS (H G E Update Medical Publishing S A, 2006)
Background/Aims: Monitoring of HBV replication level is very useful for the management of patients with chronic HBV. However, the use of the correct tools to quantify HBV-DNA levels in serum and monitor the replication of HBV is of paramount importance in terms of diagnosis, and antiviral treatment of patients with chronic HBV infection. The aim of this study was to combine the bDNA assay and HBV PCR to improve detection of viremia the patients with HBeAg-positive chronic hepatitis B infection. Methodology: In this study, 67 HBeAg-positive chronic hepatitis B patients were analyzed to determine viremia level using bDNA and HBV PCR assays. Results: Sixty-four patients with HBeAg-positive chronic hepatitis B showed positivity by conventional HBV PCR, whereas 56 subjects with HBeAg-positive chronic hepatitis B showed HBV-DNA levels by bDNA. Conclusions: The results indicated that it is reasonable to use the bDNA assay to determine HBV replicative activity first, and use conventional HBV-PCR for HBeAg-positive chronic hepatitis B patient samples that are negative in bDNA assay.
Keywords: hepatitis B; patients with HBeAg-positive chronic hepatitis B; branched DNA assay; HBVPCR